Integrating Digital Learning in English Reading Classes: Experiences of Indonesian Higher Education Lecturers - Zul Astri; Nurdin Noni; Abd Halim (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This study investigates lecturers' experiences implementing digital learning in English reading classes in Indonesian higher education. With the widespread adoption of digital technology, English reading classes that previously relied on printed texts and face-to-face interactions increasingly integrate digital tools to enhance student engagement and comprehension. This research uses a qualitative approach to explore lecturers' experiences adapting their teaching methodologies with digital tools. The purposive sample involves five lecturers teaching English reading classes at Maros Muslim University who have experience with traditional methods and digital learning, particularly during the COVID-19 pandemic. Data were collected through one-on-one interviews, providing rich, detailed accounts of how lecturers integrate digital learning into their teaching practices. Thematic analysis was used to analyze the data, following the methodological framework of Braun & Clarke (2006). This approach involved systematically identifying, analyzing, and reporting patterns (themes) within the data. The findings reveal that lecturers demonstrate high flexibility in using various digital devices such as laptops, smartphones, and tablets to meet different teaching needs. Lecturers also emphasize the importance of the interactive capabilities of digital tools, which can transform passive reading into a more dynamic and engaging experience. However, they also acknowledge the value of traditional learning materials like printed books, which remain important for tasks requiring deep engagement and critical thinking. The study highlights the need to balance digital and traditional learning resources to create inclusive and effective learning environments. The lecturers' experiences adapting to digital tools are crucial for successfully implementing digital learning and improving educational outcomes. This study provides valuable insights into the practical realities of digital learning implementation and strategies to support lecturers in this transition process.